Persepsi Pengunjung terhadap Penyelenggaraan Kuta Beach Festival Sebagai Implementasi Civic Event di Desa Adat Kuta, Kabupaten Badung, Bali - Sari, Ni Ketut Anggreni Puspa; Kusumarini, Indah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
Kuta Beach Festival is a rural event or civic event held since 2015, planned and improved by the local youth community in Kuta Village with a different theme each year. Kuta Beach Festival in 2019 is the 5th festival held by the community with “Artchelon of Atlantis”. The technic of data collection used in this thesis is interviews, questionnaires, and literature review. Samples are taken using random sampling technique (probability sample), with the number of samples of 99 respondents taken from a population of 10.147 people.The purpose of this study is to understand the visitors’ insights towards the Kuta Beach Festival as the implementation of civic event in Kuta Village in which later can be taken as considerations and be implemented as improvements in the next Kuta Beach Festival. This study applied the six dimensions of event planning: anticipation, arrival, atmosphere, appetite, activity, and amenities.The result of this study showed that visitors’ insight towards Kuta Beach Festival as an implementation of civic event in Kuta village is “Good” or “Satisfying” with an average of 3,66. However, there are 3 aspects that get sufficient assessment. They are Arrival, Appetite and Amenities.